Answer:
y = 2x + 13
y = –x – 2
Step-by-step explanation:
The options are:
y = 2x + 13
y = -x - 2
y = 3x - 5
y= -(1/2)x + 6
y = -2x - 2
The graph is shown in the figure attached. There, point (-5, 3) is shown. Replacing it into the equations we get:
y = 2(-5) + 13 = 3 (so, it is a solution)
y = -(-5) - 2 = 3 (so, it is a solution)
y = 3(-5) - 5 = -20 ≠ 3 (so, it isn't a solution)
y= -(1/2)(-5) + 6 = 8.5 ≠ 3 (so, it isn't a solution)
y = -2(-5) - 2 = 8 ≠ 3 (so, it isn't a solution)
Answer:
The function has been flipped due to the negative in front.
The function has been shifted 17 units to the left.
The function has been shifted 4.3 units down.
Step-by-step explanation:
When functions are transformed there are a few simple rules:
- Adding/subtracting inside the parenthesis to the input shifts the function left(+) and right(-).
- Adding/subtracting outside the parenthesis to the output shifts the function up(+) and down(-).
- Multiplying the function by a number less than 1 compresses it towards the x-axis.
- Multiplying the function by a number greater than 1 stretches it away from the x-axis.
- Multiplying by a negative flips the graph.
The graph of
compares to
in the following ways:
The function has been flipped due to the negative in front.
The function has been shifted 17 units to the left.
The function has been shifted 4.3 units down.
Answer:
A=235 cm 2
Step-by-step explanation:
A1=L x W
A1=9 x 20 180 + 55=235
A1=180cm 2
A2= L x W
A2=11 x 5
A2=55 cm2
144 divided by 36 is 4, so 4 yards.
Answer:
-21
Step-by-step explanation:
3t-7=5t
-7=5t-3t
-7=2t
t= -7/2
6t=?
6(-7/2)= -21